2019
DOI: 10.1111/1468-2427.12841
|View full text |Cite
|
Sign up to set email alerts
|

A Missing Citizen? Issue Based Citizenship in City‐Regional Planning

Abstract: City regions are significant sites of economic development, policymaking, and everyday living. Yet in many countries they are weakly institutionalized and therefore lack established democratic practices. This article is based on a study exploring citizen participation in city‐regional planning in Finland, where traditional participatory means have largely failed to invite and involve citizens. The analysis approaches city regions relationally, as evolving processes with a changing spatial shape and scope. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 81 publications
(119 reference statements)
0
18
0
1
Order By: Relevance
“…". On the other hand, it was confirmed that participatory mechanisms are institutionalized to a lesser degree than would be suitable [38], which is caused, among other factors, by the absence of methodological frameworks that would support participation in the planning process: [45] " . .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…". On the other hand, it was confirmed that participatory mechanisms are institutionalized to a lesser degree than would be suitable [38], which is caused, among other factors, by the absence of methodological frameworks that would support participation in the planning process: [45] " . .…”
Section: Discussionmentioning
confidence: 99%
“…Participation in land-use planning is generally required by law [23], but this often takes on a mostly pro-forma character [37], and participatory mechanisms are very weakly institutionalized [38]. This explains why, in practice, steps that reinforce participation are rarely made voluntarily, and are instead mandated by legislation [39], which merely illustrates how little importance is accorded to participation by many politicians and experts [40].…”
Section: Civic Participation: the Weak Points And Negatives In Land-use Planningmentioning
confidence: 99%
“…Tämä tarkoittaa, että heidän on vaikea toimia tietoperustaisesti ympäristökansalaisina. Vastakkainasetteluja rakentuu helposti, mikä heikentää ympäristövastuullisen kansalaisyhteiskunnan kehitystä 65,66,67 . Tilannetta voidaan parantaa tukemalla kattavaa ympäristökasvatustoimintaa.…”
Section: Investointi Ympäristökansalaisuuden Ylisukupolviseen Vahvistunclassified
“…It is here precisely that the idea of lived citizenship may help circumvent difficulties that sustain inequalities between city-regional dwellers. Instead of basing citizen participation on institutional capacity or professional expertise, city-regional citizenship can be enacted through the idea of "issue-based political agency", which centres on people's affective lived experiences and performed city-regionality (Pickard 2019; Häkli, Kallio, and Ruokolainen 2019). The premise in this approach is that, with limited motivation and resources to focus on generally politicized matters, people are inclined to direct attention to issues that concern or interest them particularly as they hold personal or social significance.…”
Section: Lived Citizenship In the Study Of City-regional Democraciesmentioning
confidence: 99%
“…As researchers we have seen the utility of this concept in our own research; how it holds potential to uncover the agency of young citizens in fresh ways (e.g. Wood 2012; 2014; Wood and Kallio 2019), enables more flexible notions of space and interrelationships of citizens (Kallio and Mitchell 2016;Wood and Black 2018), and helps foreground gaps in existing forms of political belonging (Kallio, Häkli, and Bäcklund 2015;Häkli, Kallio, and Ruokolainen 2019). Such an approach opens up a whole realm of political insight which encompasses "the feelings, experiences, practices and actions of people outside the realm of formal politics" (Pain and Smith 2008, 2).…”
Section: Introductionmentioning
confidence: 99%